Reproductive aging and pace-of-life syndromes: more active females age faster. (22nd June 2021) - Han, Chang S; Yang, Gawon
Abstract: A common pattern of reproductive aging is that reproductive performance increases during early life and reaches a peak, followed by a decline with age. Such quadratic reproductive aging patterns can differ among individuals. Moreover, if individual differences in reproductive aging patterns reflect individual-specific life-history trade-off strategies, they are also predicted to be associated with behavior according to the pace-of-life syndrome. For example, more active, aggressive, or bolder individuals may invest more in early reproduction, resulting in more rapid reproductive aging. In this study, we estimated individual differences in quadratic reproductive aging patterns and the relationship between reproductive aging and the activity of the virgin female bean bug ( Riptortus pedestris ) in the absence of mating costs. We found that the egg production of virgin females followed a parabolic trajectory with age and that individuals varied significantly in their quadratic reproductive aging patterns. In addition, we found that females that were relatively more active during early life invested in egg production more heavily at a young age and suffered from a sharper decline in egg production later in life. Thus, our results indicate that individual reproductive aging patterns may be a key component in the study of pace-of-life syndromes. We suggest that within-individual plastic characteristics of life-history traits such as reproductive aging patterns may explain the mixed results from multiple studies on pace-of-life syndromes. Abstract : More active female bean bugs invested in egg production more heavily at a young age and suffered from a sharper decline in egg production later in life. This indicates that the plastic characteristics of life-history traits such as reproductive aging patterns should be incorporated in studies integrating behavioral traits with life-history traits.